The Effect of Fixed Orthodontic Treatment on Salivary Component: Efek Perawatan Ortodonti Cekat Terhadap Komponen Saliva - Lindawati, Yumi; Sufarnap, Erliera; Munawarah, Wihda (TALENTA, 2019)
Saliva is a complex oral fluid that has an important role on maintaining oral health. Mechanical stimulation such as fixed orthodontic appliance can alter saliva characteristics. The objective of this study is to recognize the components of saliva in a fixed orthodontic treatment. This study in an observational analytic study with a cross sectional approach, the sample is stimulated saliva of 44 subjects (18-25 years of age) consisting of subjects without orthodontic appliance and subjects with orthodontic appliances. Sample is obtained by purposive sampling based on inclusion and exclusion criteria. The result of this study is to understand significant differences in salivary flow, pH, buffer capacity and calcium between subjects between subjects with and without orthodontic appliances (p=0,001). The conclusion in this study is that fixed orthodontic appliance can increase salivary flow, pH, buffer capacity and calcium.